Sidelobe Level Suppression in Linear and Planar Phased Arrays Using Grey Wolf Optimization With Local Search Refinements - Muhammad Athallah Adriansyah; Aditya Inzani Wahdiyat; Ismi Rosyiana Fitri; Noor Asniza Murad; Catur Apriono (IEEE Access)
Phased array antennas play a critical role in satellite communication systems, where minimizing peak sidelobe levels (PSLL) is essential to prevent interference and enhance signal quality. This paper presents a novel hybrid optimization approach, grey wolf optimizer with Nelder-Mead local search (GWO-NM), to suppress PSLL effectively in both linear antenna arrays (LAA) and planar antenna arrays (PAA). The proposed method combines the global search capability of grey wolf optimizer (GWO) with the Nelder-Mead local refinement to address the PSLL suppression challenge. The optimization process was applied to both 32-element and 100-element LAA, achieving PSLL reductions to −52.63 dB and −56.39 dB, respectively, and these results are also extended to the corresponding PAA configuration. The results were further validated through full-wave electromagnetic simulations in CST Microwave Studio 2024, considering practical effects such as mutual coupling and material losses. Also, this suppression comes with trade-offs, including a widened first null beamwidth from 18.34° to 19.78° for the 32-element arrays and from 6.47° to 9.71° for the 100-element arrays in both LAA and their corresponding PAA compared to the conventional algorithm, along with a marginal decrease of 0.5-1 dB in directivity observed in electromagnetic simulations. The GWO-NM algorithm outperformed other metaheuristic optimization techniques, including PSO, ACO, CSO, ABCO, and conventional GWO, demonstrating superior sidelobe suppression across different array configurations while maintaining an acceptable trade-off with other key radiation parameters.